The influence of crop rotation on soil fertility and yield of spring wheat in forest-steppe zone of the Tuva Republic - T. F. Zharova (Аграрная наука Евро-Северо-Востока, 2016)
The results of the study on the effects of crop rotation with different kinds of fallows on spring wheat yield on dark brown soils in forest-steppes of Republic of Tuva are presented. It was found that after rotation the humus content increased in crop rotation with green manure fallows (melilot, peas) by 0.6-0.13%; decreased - in grain-fallow control by 0.46% (abs.). Soil supply with labile P2O5 was average in 2006 whereas in 2014 it was extremely low in control crop rotation and grain crop rotation and average in other types of rotation. Supply with exchange K2O increased (from average in 2006 to high in 2014) in grain-fallow and green-manure with manure (30 t/ha) crop rotation. At the precursor "pure fallow" the density of composition in the soil layers 0-10 and 10-20 cm under wheat increased insignificantly by 1.5-3.7 %, in other variants - decreased by 3-8%. The greatest decrease in the soil density (7-8%) was observed in the 0-10 cm layer after green-manure crops. After them the yield of wheat Kantegirskaya 89 was higher by 0.24-0.28 t/ha, Chagytay - 0.10-0,05 t/ha in comparison with pure unfertilized fallow. In rotation with occupied fallow grain exit of Kantegirskaya 89 decreased in comparison with pure fallow by 0.45 t/ha; with green manure fallow - by 0.69-0.73 t/ha; of variety Chagytay respectively by 0.14 and 0.19-0.25 t /ha